Sunburn assessment: A critical appraisal of methods and techniques for characterizing the damage to apple fruit - Racskó, J. (International Journal of Horticultural Science, 2010)
Many methods and techniques have been introduced for measuring alterations in the fruit and in its surrounding environment related to sunburn incidence. The research objectives, fruit materials and the environment to be evaluated dictate the methods to follow. These procedures are either non-destructive and involve techniques that allow us to track the course of sunburn development and related environmental parameters, or destructive and involve the removal of fruit from the tree for field/laboratory measurements. Techniques employed can be used for pre-symptomatic monitoring (before symptoms become visible) or characterizing the symptoms already present. The principles behind the measurements and their usefulness for sunburn assessments are discussed and critically evaluated in this review paper. Descriptions and evaluations of the methods and techniques were made in the following groups: 1. Thermal measurements; 2. Visual assessments; 3. Fruit quality measurements; 4. Measurements of physiological and biochemical alterations; and 5. Practical evaluation of sunburn damage. Thermal measurements involve methods tracking the ambient temperature and fruit surface temperature, and their relation to sunburn formation. Visual assessments cover all measuring techniques (skin color, chlorophyll fluorescence, radiation reflection, electron microscopy) that are able to detect changes on/in the fruit skin related to sunburn formation. Fruit quality measurements are used to point out differences in qualities (soluble solids, firmness, titratable acidity, and water content) between unaffected and sunburned areas of the fruit. The measurements of physiological and biochemical alterations (gas exchange, pigment analysis, enzyme activity, gene expression) give us a better insight to the mechanism of sunburn formation. Practical evaluations involve many procedures that are used by scientists to characterize the susceptibility of cultivars, evaluate protection technology, etc. For this purpose, the following methods are in use: expressing the percentage of the total fruit surface area affected by sunburn or the percentage of the total number of fruits damaged on the tree, or even a scale based on the severity of the symptoms occurred. All assessing methods and techniques described here have their pros and cons as well as their specific applicability, therefore any of these cannot be favored to use exclusively for assessing sunburn incidence. The combination of these techniques will be the best choice to meet a given research objective perfectly.